PEMIKIRAN EKONOMI ABU YUSUF DALAM KITAB AL-KHARAJ - Martina Nofra Tilopa (Al-Intaj)
The economic idea of Abu Yusuf pointed out is concerning State and economic activity, kharaj (Taxation), public finance and price mechanism.. He always stressed the importance of meeting the needs of the people and developing various projects that are oriented towards the general welfare. Next on taxation, in setting tax rates he recommends the use of the system muqasamah (proportional tax) than the system Misahah (Fixed Tax). In the case of kharaj administration, Abu Yusuf rejects the practice of taqbil (qabalah). Taqbil is a kharaj collection system where a person is usually from a local inhabitant, volunteers to the ruler to be responsible for collecting and gathering kharaj in his territory. Furthermore, on public finances he believes that State Revenue in Daulah Islamiyah is divided into three categories, namely ghanimah, adaqah, and fa'I treasures (jizyah, 'usyur and kharaj). And in the price mechanism he argues that prices may remain expensive when supplies are abundant while goods will be cheap even if inventory is reduced.